Analisis Penggunaan Model Pembelajaran Problem Based Learning Dengan Media Konkret Pada Mata Pelajaran Ipas Peserta Didik Kelas V Sdn Mojosongo 1 Surakarta Tahun Pelajaran 2024/2025 - Pratama, Fariska Prianda Putri; Handini, Oktiana; Hanafi, Muhammad Faruq (JURNAL MANAJEMEN PENDIDIKAN, 2025)
ANALYSIS OF THE USE OF PROBLEM BASED LEARNING MODEL WITH CONCRETE MEDIA IN SOCIAL AND NATURAL SCIENCES LESSONS FOR FIFTH-GRADE STUDENTS AT SDN MOJOSONGO 1 SURAKARTA, ACADEMIC YEAR 2024/2025Fifth-grade students at SDN Mojosongo 1 Surakarta studied Natural and Social Sciences (IPAS) using a Problem Based Learning (PBL) model with concrete media during the 2024/2025 school year. In this approach, teachers didn’t just deliver the material—they guided students to think actively, discuss ideas, and find solutions to the problems given. The learning process was observed through direct classroom observation, interviews with students and teachers, and documentation to get a clear picture of how lessons unfolded. The results were quite positive. Students were more enthusiastic because they could see and try out the material directly. Teachers also found it easier to monitor student progress and provide help when needed. Some factors supported this engaging learning, such as student enthusiasm, teacher creativity, and the availability of interesting learning media. However, there were also challenges, like limited time and differences in student abilities, which sometimes required extra attention for certain students. This approach helped students understand IPAS concepts more easily while also developing critical thinking, creativity, and problem-solving skills. Learning became more enjoyable, interactive, and tangible, making classroom experiences more lively and meaningful for everyone.